Manufacturing method for RTB sintered magnets and RTB sintered magnets

JP7661811B2Active Publication Date: 2025-04-15PROTERIAL LTD
View PDF 7 Cites 0 Cited by

Patent Information

Application Number
JP2021114084
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Priority Date
2021-03-23
Filing Date
2021-07-09
Publication Date
2025-04-15
Estimated Expiration
2041-07-09

AI Technical Summary

Benefits of technology

【0018】 本開示の実施形態によれば、重希土類元素の使用量を低減しつつ、BrとHcJのバランスに優れたR-T-B系焼結磁石の製造方法よびR-T-B系焼結磁石を提供することができる。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007661811000025
    Figure 0007661811000025
  • Figure 0007661811000026
    Figure 0007661811000026
  • Figure 0007661811000027
    Figure 0007661811000027
Patent Text Reader

Abstract

To provide a manufacturing method of an R-T-B system sintered magnet having an excellent balance between Br and HcJ while reducing the amount of heavy rare earth element RH used, an R-T-B system sintered magnet, and a manufacturing method thereof.SOLUTION: A manufacturing method of an R-T-B system sintered magnet includes a step S10 of preparing an R-T-B based sintered magnet material (R is a rare earth element, T is at least one selected from the group consisting of Fe, Co, Al, Mn and Si, and necessarily contains Fe), a step S20 of preparing an RL-RH-B-M alloy, and a diffusion step S30 of adhering and heating at least a portion of the RL-RH-B-M alloy to at least a portion of the surface of the R-T-B based sintered magnet material. The RL content of the RL-RH-B-M alloy is 50 mass% or more and 95 mass% or less, the RH content is 45 mass% or less (including 0 mass%), and the B content is 0.1 mass% or more and 3.0 mass% or less, and the M content is 4 mass% or more and 49.9 mass% or less.SELECTED DRAWING: Figure 2
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a method for producing an RTB based sintered magnet, and to an RTB based sintered magnet. [Background technology]

[0002] RTB sintered magnets (R is a rare earth element, T is mainly Fe, and B is boron) are known as the most high-performance permanent magnets, and are used in a variety of motors and home appliances, including voice coil motors (VCM) for hard disk drives, motors for electric vehicles (EV, HV, PHV, etc.), and motors for industrial equipment. RTB sintered magnets contribute to energy conservation and reduced environmental impact by making various motors smaller and lighter.

[0003] RTB sintered magnets are mainly R2T 14 It is composed of a main phase made of B compounds and a grain boundary phase located at the grain boundary of this main phase. 14 B compounds are ferromagnetic materials with high saturation magnetization and anisotropic magnetic field, and form the basis of the properties of RTB sintered magnets.

[0004] RTB sintered magnets have a coercive force H cJ (Hereafter, simply "H cJ This causes a problem of irreversible thermal demagnetization due to the decrease in the magnetization temperature (H), which is particularly important for RTB sintered magnets used in electric vehicle motors. cJ i.e., higher H at room temperature cJ It is required that the applicant have:

[0005] R2T 14 When light rare earth elements (mainly Nd and Pr) in the B-type compound phase are replaced by heavy rare earth elements (mainly Dy and Tb), H cJ However, H cJ While R2T 14 The saturation magnetization of the B-type compound phase decreases, so the residual magnetic flux density B r (Hereinafter, simply "Br There is a problem in that the quality of the product (called "energy permeability") decreases.

[0006] Patent Document 1 describes a method of supplying a heavy rare earth element such as Dy to the surface of a sintered magnet made of an RTB alloy while diffusing the heavy rare earth element RH into the interior of the sintered magnet. The method described in Patent Document 1 diffuses Dy from the surface to the interior of an RTB sintered magnet, and cJ By concentrating Dy only in the outer periphery of the main phase crystal grains, which is effective in improving B r While suppressing the decline of cJ can be obtained.

[0007] In Patent Document 2, a specific composition of R-Ga-Cu alloy is brought into contact with the surface of an RTB sintered compact and heat-treated to control the composition and thickness of the grain boundary phase in the RTB sintered magnet, thereby producing H cJ It is described that the above-mentioned method improves the above-mentioned performance. [Prior art documents] [Patent documents]

[0008] [Patent Document 1] International Publication No. 2007 / 102391 [Patent Document 2] International Publication No. 2016 / 133071 Summary of the Invention [Problem to be solved by the invention]

[0009] However, in recent years, the amount of expensive heavy rare earth elements used has been reduced, particularly in electric vehicle motors, while the amount of B r and H cJ Excellent balance of (B r While suppressing the decline of cJ There is a demand for obtaining RTB sintered magnets.

[0010] Various embodiments of the present disclosure provide a method for reducing the amount of heavy rare earth elements used while increasing the amount of B r and H cJThe present invention provides a method for producing an RTB-based sintered magnet with an excellent balance of properties and a RTB-based sintered magnet. [Means for solving the problem]

[0011] In an exemplary embodiment, a method for producing an RTB based sintered magnet according to the present disclosure includes the steps of preparing an RTB based sintered magnet material (R is a rare earth element and necessarily includes at least one selected from the group consisting of Nd, Pr, and Ce, T is at least one selected from the group consisting of Fe, Co, Al, Mn, and Si, and necessarily includes Fe), and producing an RL-RH-BM based alloy (RL is a light rare earth element and necessarily includes at least one selected from the group consisting of Nd, Pr, and Ce, RH is at least one selected from the group consisting of Tb, Dy, and Ho, B is boron, and M is Cu, Ga, Fe, Co, Ni, Al, A, and B). the RL-RH-BM alloy has an RL content of 50 mass% or more and 95 mass% or less, an RH content of 45 mass% or less (including 0 mass%), a B content of 0.1 mass% or more and 3.0 mass% or less, and an M content of 4 mass% or more and 49.9 mass% or less.

[0012] In one embodiment, the molar ratio of T to B, [T] / [B], in the RTB based sintered magnet material is greater than 14.0 and not greater than 15.0.

[0013] In one embodiment, M of the RL-RH-BM alloy contains at least one of Cu, Ga, and Fe, and the total content of Cu, Ga, and Fe in M ​​is 80 mass % or more.

[0014] In an exemplary embodiment, the RTB based sintered magnet of the present disclosure contains R (R is a rare earth element and necessarily includes at least one selected from the group consisting of Nd, Pr, and Ce), T (T is at least one selected from the group consisting of Fe, Co, Al, Mn, and Si and necessarily includes Fe), B, and at least one selected from the group consisting of Cu, Ga, Ni, Ag, Zn, and Sn, and the molar ratio of T to B [T] / [B] in the surface portion of the magnet is lower than the molar ratio of T to B [T] / [B] in the central portion of the magnet.

[0015] In one embodiment, the magnet includes a portion in which the B concentration gradually decreases from the magnet surface toward the magnet interior.

[0016] In one embodiment, the molar ratio of T to B [T] / [B] at the surface of the magnet is lower by 0.2 or more than the molar ratio of T to B [T] / [B] at the center of the magnet.

[0017] In one embodiment, the RTB based sintered magnet has a Tb content of less than 0.5 mass % (including 0 mass %). Effect of the Invention

[0018] According to the embodiment of the present disclosure, the amount of heavy rare earth elements used is reduced while B r and H cJ It is therefore possible to provide a method for producing an RTB based sintered magnet that has an excellent balance of these properties, and an RTB based sintered magnet. [Brief description of the drawings]

[0019] [Figure 1A] FIG. 2 is an enlarged schematic cross-sectional view of a portion of an RTB based sintered magnet. [Figure 1B] 1B is a cross-sectional view showing a further enlarged schematic view of the dashed rectangular region in FIG. 1A. [Diagram 2] 1 is a flowchart showing an example of steps in a method for producing an RTB based sintered magnet according to the present disclosure. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0020] First, the basic structure of the RTB based sintered magnet according to the present disclosure will be described. The RTB based sintered magnet has a structure in which powder particles of raw alloys are bonded together by sintering, and is mainly 14 It is composed of a main phase made of B compound particles and a grain boundary phase located at the grain boundaries of this main phase.

[0021] FIG. 1A is a cross-sectional view showing an enlarged schematic view of a portion of an RTB sintered magnet, and FIG. 1B is a cross-sectional view showing an enlarged schematic view of the dashed rectangular region in FIG. 1A. In FIG. 1A, an arrow of 5 μm in length is shown as an example for reference, showing the reference length of the size. As shown in FIG. 1A and FIG. 1B, an RTB sintered magnet is mainly 14 The grain boundary phase 14 is composed of a main phase 12 made of a B compound and a grain boundary phase 14 located at the grain boundary portion of the main phase 12. As shown in FIG. 1B, the grain boundary phase 14 is composed of two R2T 14 The two-particle grain boundary phase 14a in which B compound grains are adjacent, and the three R2T 14 The B compound grains include adjacent grain boundary triple junctions 14b. The typical main phase crystal grain size is 3 μm or more and 10 μm or less in terms of the average circle equivalent diameter of the magnet cross section. 14 B compounds are ferromagnetic materials with high saturation magnetization and anisotropic magnetic field. Therefore, in RTB sintered magnets, the R2T 14 By increasing the proportion of B compounds, r It can improve R2T 14 In order to increase the ratio of B compounds, the amounts of R, T, and B in the raw alloy should be adjusted to R2T 14 It is sufficient to approach the stoichiometric ratio of the B compound (amount of R:amount of T:amount of B = 2:14:1). In addition, the main phase R2T 14It is known that by substituting a part of the R in B compounds with heavy rare earth elements such as Dy, Tb, and Ho, the saturation magnetization can be reduced while the anisotropy field of the main phase can be increased. In particular, the outer shell of the main phase that contacts the two-particle grain boundary phase is likely to be the starting point of magnetization reversal, so the heavy rare earth diffusion technology, which can preferentially substitute heavy rare earth elements in the outer shell of the main phase, can efficiently achieve high H while suppressing the decrease in saturation magnetization. cJ is obtained. On the other hand, by controlling the magnetism of the two-grain grain boundary phase 14a, a high H cJ Specifically, by lowering the concentration of magnetic elements (Fe, Co, Ni, etc.) in the two-particle grain boundary phase, the two-particle grain boundary phase becomes closer to non-magnetic, weakening the magnetic coupling between the main phases and suppressing magnetization reversal.

[0022] As a result of the inventor's investigation, the method described in Patent Document 2 has been found to be capable of reducing the amount of heavy rare earth elements used while achieving high H cJ Although RTB sintered magnets with B r It was found that a decrease in B r This decrease is believed to be due to the fact that the amount of R (especially RL) near the magnet surface increases due to diffusion, which reduces the volume ratio of the main phase near the magnet surface. Based on this knowledge, the inventors conducted further research and discovered that it is possible to suppress the decrease in the volume ratio of the main phase near the magnet surface by diffusing a narrow, specific range of B together with specific ranges of RL and M from the surface of the RTB sintered magnet material through the grain boundaries into the interior of the magnet material. This allows the amount of B caused by diffusion to be reduced. r This allows the use of less heavy rare earth elements while suppressing the decrease in B r and H cJIt is possible to obtain an RTB-based sintered magnet with an excellent balance of R and M. This is thought to be because the Fe present in the grain boundaries near the magnet surface and the RL introduced by diffusion form the main phase with the B also introduced by diffusion. The RTB-based sintered magnet obtained in this way contains R, T, B and M, and it was found that the molar ratio of T to B [T] / [B] at the magnet surface is lower than the molar ratio of T to B [T] / [B] at the magnet center. The fact that the molar ratio of T to B [T] / [B] at the magnet surface is lower than the molar ratio of T to B [T] / [B] at the magnet center indicates that the magnet surface has a relatively higher amount of B than the magnet center. This suppresses the decrease in the volume ratio of the main phase at the magnet surface due to diffusion, and therefore the amount of B is reduced. r and H cJ Therefore, an RTB sintered magnet with excellent balance can be obtained.

[0023] The method for producing an RTB based sintered magnet according to the present disclosure includes step S10 of preparing an RTB based sintered magnet material, and step S20 of preparing an RL-RH-BM based alloy, as shown in Fig. 2. The order of step S10 of preparing the RTB based sintered magnet material and step S20 of preparing the RL-RH-BM based alloy may be arbitrary. As shown in FIG. 2, the method for producing an RTB based sintered magnet according to the present disclosure further includes a diffusion step S30 of adhering at least a portion of the RL-RH-BM based alloy to at least a portion of the surface of the RTB based sintered magnet material, and heating the material at a temperature of 700° C. or higher and 1100° C. or lower in a vacuum or inert gas atmosphere.

[0024] In this disclosure, the RTB based sintered magnet before and during the diffusion process is referred to as the "RTB based sintered magnet material", and the RTB based sintered magnet after the diffusion process is simply referred to as the "RTB based sintered magnet".

[0025] (Preparation of RTB sintered magnet material) In the RTB sintered magnet material, R is a rare earth element and necessarily contains at least one selected from the group consisting of Nd, Pr, and Ce, and T is at least one selected from the group consisting of Fe, Co, Al, Mn, and Si and necessarily contains Fe. The content of R is, for example, 27 mass% or more and 35 mass% or less of the entire RTB sintered magnet material. The content of Fe relative to the entire T is 80 mass% or more. If R is less than 27 mass%, the liquid phase is not sufficiently generated during the sintering process, and it may be difficult to sufficiently densify the sintered body. On the other hand, if R exceeds 35 mass%, grain growth occurs during sintering, and H cJ R is preferably 28 mass% or more and 33 mass% or less.

[0026] The RTB based sintered magnet material has, for example, the following composition range. R: 27-35 mass%, B: 0.80 to 1.20 mass%, Ga: 0 to 1.0 mass%, X: 0 to 2 mass% (X is at least one of Cu, Nb, and Zr), T: Contains 60 mass% or more.

[0027] Preferably, in the RTB based sintered magnet material, the molar ratio of T to B, [T] / [B], is greater than 14.0 and not greater than 15.0. cJ In the present disclosure, [T] / [B] is the ratio of [T], which is the sum of the analytical values ​​(mass%) of each element constituting T (at least one selected from the group consisting of Fe, Co, Al, Mn, and Si, where T necessarily contains Fe and the content of Fe in the entire T is 80 mass% or more) divided by the atomic weight of each element, to [B], which is the analytical value (mass%) of B divided by the atomic weight of B. The condition that the molar ratio [T] / [B] exceeds 14.0 is satisfied when the main phase (R2T 14It is more preferable that the molar ratio [T] / [B] is 14.3 or more and 15.0 or less. cJ The B content is preferably 0.9 mass % or more and less than 1.0 mass % of the entire RTB sintered body.

[0028] The RTB sintered magnet material can be prepared by a general manufacturing method for RTB sintered magnets, such as Nd-Fe-B sintered magnets. For example, a raw material alloy produced by strip casting or the like is milled into powder with a particle size D 50 The powder can be prepared by crushing the powder to a size of 2.0 μm to 5.0 μm, molding the powder in a magnetic field, and sintering the powder at a temperature of 900° C. to 1100° C. to produce a sintered body. 50 By grinding the powder to 2.0 μm or more and 5 μm or less, high magnetic properties can be obtained. This is thought to be because the particle size of the powder is reflected in the crystal grain size of the sintered body, which also affects diffusion. 50 The thickness is 2.5μm or more and 4.0μm or less. It is possible to reduce precious RH while suppressing deterioration of productivity and obtain more B r and H cJ In addition, it is possible to obtain an RTB sintered magnet with an excellent balance of the above-mentioned D 50 is the particle size at which the cumulative particle size distribution (volume basis) from the small diameter side becomes 50% in the particle size distribution obtained by the laser diffraction method using the air flow dispersion method. 50 can be measured, for example, using a particle size distribution measuring device "HELOS&RODOS" manufactured by Sympatec under the conditions of dispersion pressure: 4 bar, measurement range: R2, and measurement mode: HRLD.

[0029] (Preparing RL-RH-BM alloy) In the RL-RH-BM alloy, RL is a light rare earth element and necessarily contains at least one selected from the group consisting of Nd, Pr, and Ce, RH is at least one selected from the group consisting of Tb, Dy, and Ho, B is boron, and M is at least one selected from the group consisting of Cu, Ga, Fe, Co, Ni, Al, Ag, Zn, Si, and Sn. The content of RL is 50 mass% or more and 95 mass% or less of the entire RL-RH-BM alloy. Examples of light rare earth elements include La, Ce, Pr, Nd, Pm, Sm, and Eu. The content of RH is 45 mass% or less (including 0 mass%) of the entire RL-RH-BM alloy. In other words, RH may not be contained. The content of B is 0.1 mass% or more and 3.0 mass% or less of the entire RL-RH-BM alloy. The content of M is 4 mass% or more and 49.9 mass% or less of the entire RL-RH-BM alloy. Typical examples of RL-RH-BM alloys include TbNdPrBCu alloy, TbNdCePrBCu alloy, TbNdPrBCuFe alloy, TbNdBGa alloy, TbNdPrBGaCu alloy, TbNdBGaCuFe alloy, and NdPrTbBCuGaAl alloy. In addition to the above elements, it may contain small amounts of elements such as inevitable impurities, such as Mn, O, C, and N. For example, C can be contained by using Fe-B or B4C as a B source.

[0030] If RL+RH is less than 50 mass%, it becomes difficult for RH, B, and M to be introduced into the RTB sintered magnet material, and H cJ If the content of RL+RH exceeds 95 mass%, the alloy powder during the manufacturing process of the RL-RH-BM alloy becomes very active. As a result, the alloy powder may be significantly oxidized or ignite. The content of RL+RH is preferably 70 mass% or more and 80 mass% or less of the entire RL-RH-BM alloy. Higher H cJ can be obtained.

[0031] When RH exceeds 45 mass%, the amount of rare heavy rare earth elements used can be reduced while B r and H cJIt is not possible to obtain an RTB sintered magnet with a good balance between the RL content and the RH content. Preferably, the RH content is 20 mass% or less of the entire RL-RH-BM alloy. Also, the total content of the RL and the RH in the RL-RH-BM alloy is preferably 55 mass% or more of the entire RL-RH-BM alloy. This results in a high H cJ In addition, when the content (mass%) of RL in the RL-RH-BM alloy is [RL] and the content of RH is [RH], it is preferable to satisfy the relationship [RL]>1.5×[RH]. This allows the amount of heavy rare earth elements to be reduced while the amount of B is increased. r and H cJ Therefore, an RTB sintered magnet with excellent balance can be obtained.

[0032] If B is less than 0.1 mass%, it may not be possible to suppress the decrease in the volume ratio of the main phase near the magnet surface. If it exceeds 3.0 mass%, the H caused by RL and B may be increased. cJ The improvement effect may be reduced. Preferably, the B content is 0.5 mass% or more and 2.0 mass% or less of the entire RL-RH-BM alloy. r and H cJ It is possible to obtain an R-TB sintered magnet with an excellent balance of these properties.

[0033] If M is less than 4 mass%, RL, B, and RH are difficult to incorporate into the two-particle grain boundary phase, and H cJ If it exceeds 49.9 mass%, the content of RL and B will decrease and H cJ The content of M is preferably 7 mass% or more and 15 mass% or less of the entire RL-RH-BM alloy. cJ Preferably, M of the RL-RH-BM alloy contains at least one of Cu, Ga, and Fe, and the total content of Cu, Ga, and Fe in M ​​is 80 mass% or more, so that a higher H cJ can be obtained.

[0034] The method for producing the RL-RH-BM alloy is not particularly limited. It may be produced by roll quenching or casting. These alloys may be pulverized to produce alloy powder. It may also be produced by a known atomization method such as centrifugal atomization, rotating electrode method, gas atomization, or plasma atomization.

[0035] (Diffusion process) At least a part of the prepared RL-RH-BM alloy is attached to at least a part of the surface of the RTB sintered magnet material prepared as described above, and a diffusion step is performed in which the material is heated in a vacuum or inert gas atmosphere at a temperature of 700°C to 1100°C. As a result, a liquid phase containing RL, B, (RH) and M is generated from the RL-RH-BM alloy, and the liquid phase is diffused from the surface of the sintered magnet material to the inside via the grain boundaries in the RTB sintered magnet material. The amount of the RL-RH-BM alloy attached to the RTB sintered magnet material is preferably 1 mass% to 8 mass%, and more preferably 1 mass% to 5 mass%. By setting the amount within this range, it is possible to more reliably reduce the amount of heavy rare earth elements used while achieving a high H cJ It is possible to obtain an RTB based sintered magnet having the above properties.

[0036] The heating temperature in the diffusion step is preferably 700° C. or higher and 1100° C. or lower. If the temperature is lower than 700° C., high H cJ On the other hand, if the temperature exceeds 1100℃, H cJ The heating temperature in the diffusion step is preferably 800°C or higher and 1000°C or lower. cJ It is also preferable to cool the RTB sintered magnet that has been subjected to the diffusion step (700°C or more and 1100°C or less) from the temperature at which the diffusion step was performed to 300°C at a cooling rate of 15°C / min or more. cJ can be obtained.

[0037] The diffusion process can be carried out by disposing an RL-RH-BM alloy of any shape on the surface of the RTB sintered magnet material and using a known heat treatment device. For example, the surface of the RTB sintered magnet material can be covered with a powder layer of the RL-RH-BM alloy and then the diffusion process can be carried out. For example, a coating process of coating an adhesive on the surface to be coated and a process of attaching the RL-RH-BM alloy to the area coated with the adhesive may be carried out. Examples of adhesives include PVA (polyvinyl alcohol), PVB (polyvinyl butyral), and PVP (polyvinylpyrrolidone). When the adhesive is a water-based adhesive, the RTB sintered magnet material may be preheated before coating. The purpose of the preheating is to remove excess solvent to control the adhesive strength and to attach the adhesive uniformly. The heating temperature is preferably 60 to 200°C. In the case of a highly volatile organic solvent-based adhesive, this process may be omitted. Also, for example, a slurry in which the RL-RH-BM alloy is dispersed in a dispersion medium may be applied to the surface of the RTB sintered magnet material, and then the dispersion medium may be evaporated to adhere the RL-RH-BM alloy to the RTB sintered magnet material. Examples of the dispersion medium include alcohol (such as ethanol), aldehydes, and ketones. Furthermore, so long as at least a portion of the RL-RH-BM alloy is attached to at least a portion of the sintered RTB magnet material, there is no particular restriction as to the position where it is disposed.

[0038] (Heat treatment process) Preferably, as shown in Fig. 2, the RTB based sintered magnet that has been subjected to the diffusion step is subjected to a heat treatment in a vacuum or inert gas atmosphere at a temperature of 400°C to 900°C, which is lower than the temperature used in the diffusion step. The heat treatment may be performed multiple times. By performing the heat treatment, a higher H cJ can be obtained.

[0039] (RTB sintered magnet) The RTB based sintered magnet obtained by the manufacturing method of the present disclosure contains R (R is a rare earth element and always includes at least one selected from the group consisting of Nd, Pr, and Ce), T (T is at least one selected from the group consisting of Fe, Co, Al, Mn, and Si and always includes Fe), B, and at least one selected from the group consisting of Cu, Ga, Ni, Ag, Zn, and Sn, and the molar ratio of T to B [T] / [B] at the surface of the magnet is lower than the molar ratio of T to B [T] / [B] at the center of the magnet. In addition, the RTB based sintered magnet of the present disclosure includes a portion where the B concentration gradually decreases from the magnet surface toward the magnet's interior.

[0040] The RTB based sintered magnet of the present disclosure may have, for example, the following composition.

[0041] R: 26.8mass% or more and 31.5mass% or less, B: 0.90mass% or more and 0.97mass% or less, M: 0.05 mass% or more and 1.0 mass% or less (M is at least one selected from the group consisting of Ga, Cu, Zn, and Si); M1: 0 mass% or more and 2.0 mass% or less (M1 is at least one selected from the group consisting of Al, Ti, V, Cr, Mn, Ni, Zr, Nb, Mo, Ag, In, Sn, Hf, Ta, W, Pb, and Bi) The balance consists of T (T is Fe or Fe and Co) and unavoidable impurities. The present disclosure provides a method for reducing the amount of heavy rare earth elements used while increasing the amount of B r and H cJ Therefore, it is preferable that Tb in particular be less than 5 mass% (including 0 mass%) of the entire RTB based sintered magnet, more preferably 1 mass% or less, and even more preferably 0.5 mass% or less.

[0042] In this disclosure, the surface portion of the magnet refers to the portion located at a depth of 300 μm from the outermost surface of the magnet, and the central portion of the magnet refers to the portion located at the center of the magnet.

[0043] The molar ratio of T to B [T] / [B] at the magnet surface is lower than the molar ratio of T to B [T] / [B] at the magnet center, which indicates that the amount of B is relatively higher at the magnet surface than at the magnet center. By making the molar ratio of T to B [T] / [B] at the magnet surface lower than the molar ratio of T to B [T] / [B] at the magnet center, the decrease in the volume ratio of the main phase at the magnet surface due to diffusion is suppressed, and the amount of B is reduced. r and H cJ It is preferable that the molar ratio of T to B [T] / [B] at the surface of the magnet is at least 0.2 lower than the molar ratio of T to B [T] / [B] at the center of the magnet. r and H cJ It is more preferable that the molar ratio of T to B [T] / [B] at the surface of the magnet is 0.4 or more lower than the molar ratio of T to B [T] / [B] at the center of the magnet. r and H cJ In addition, if the molar ratio of T to B [T] / [B] at the surface of the magnet is lower than the molar ratio of T to B [T] / [B] at the center of the magnet by more than 3.0, the H cJ Therefore, it is preferable that the molar ratio of T to B [T] / [B] at the surface of the magnet is 0.2 to 3.0 (more preferably 0.4 to 3.0) lower than the molar ratio of T to B [T] / [B] at the center of the magnet.

[0044] The fact that an RTB sintered magnet contains a portion where the B concentration gradually decreases from the magnet surface toward the magnet's interior indicates that B is in a state where it has diffused from the magnet surface to the magnet's interior. This state can be confirmed, for example, by cutting out an individual piece, such as 1 x 1 x 1 mm, from the magnet surface to the magnet's interior and performing a component analysis using inductively coupled plasma optical emission spectroscopy (ICP-OES).

[0045] Furthermore, the RTB based sintered magnet of the present disclosure may include a portion where the RH (e.g. Tb) concentration gradually decreases from the magnet surface toward the magnet interior. The fact that the RTB based sintered magnet includes a portion where the RH concentration gradually decreases from the magnet surface toward the magnet interior indicates that RH is in a state where it has diffused from the magnet surface to the magnet interior. Whether or not the RTB based sintered magnet includes a portion where the RH concentration gradually decreases from the magnet surface toward the magnet interior can be confirmed in the same manner as for the gradual decrease in B concentration described above. EXAMPLES

[0046] The present invention will be described in more detail with reference to examples, but the present invention is not limited thereto.

[0047] Experimental Example 1 [Preparing RTB sintered magnet material (magnetic material)] Each raw material was weighed and cast by strip casting so as to obtain the composition of the magnet material (excluding unavoidable impurities) shown in Table 1, as indicated by symbols 1-A to 1-D, to obtain flake-shaped raw alloys having a thickness of 0.2 to 0.4 mm. The obtained flake-shaped raw alloys were subjected to hydrogen pulverization, followed by dehydrogenation treatment in which they were heated to 550°C in a vacuum and then cooled to obtain coarsely pulverized powder. The obtained coarsely pulverized powder was then pulverized using an airflow pulverizer (jet mill device) to obtain finely pulverized powder (alloy powder) with a particle size D50 of 3 μm. The particle size D50 is the volume center value (volume-based median diameter) obtained by laser diffraction using the airflow dispersion method.

[0048] The finely pulverized powder was molded in a magnetic field to obtain a green body. The molding device used was a so-called perpendicular magnetic field molding device (horizontal magnetic field molding device) in which the magnetic field application direction and the pressure direction are perpendicular to each other.

[0049] The obtained green body was sintered in a vacuum at 1000°C to 1050°C (a temperature at which sufficient densification by sintering occurs for each sample) for 4 hours, and then rapidly cooled to obtain a magnetic material. The density of the obtained magnetic material was 7.5 Mg / m 3That was all. The results of the composition of the obtained magnet material are shown in Table 1. Each component in Table 1 was measured using inductively coupled plasma optical emission spectroscopy (ICP-OES). The oxygen content of the magnet material was measured using a gas fusion-infrared absorption method, and it was confirmed that all were around 0.2 mass%. Furthermore, C (carbon content) was measured using a gas analyzer using a combustion-infrared absorption method, and it was confirmed that it was around 0.1 mass%. In Table 1, "[T] / [B]" is the ratio (a / b) of (a) the analysis value (mass%) of each element (here, Fe, Al, Si, Mn) constituting T divided by the atomic weight of the element, and the total of these values ​​is calculated, and (b) the analysis value (mass%) of B divided by the atomic weight of B. The same applies to all the following tables. The sum of each composition, oxygen content, and carbon content in Table 1 does not equal 100 mass%. This is because impurity elements other than those listed in the table are included. The same applies to other tables.

[0050] [Table 1]

[0051] [Preparation of RL-RH-BM alloy] Each element was weighed so as to obtain the composition of the RL-RH-BM alloys and the composition of the alloys not containing B shown in Table 2, as indicated by symbols 1-a to 1-f, and the raw materials were melted and ribbon or flake-shaped alloys were obtained by a single-roll ultra-quenching method (melt spinning method). The obtained alloys were pulverized in an argon atmosphere using a mortar to prepare the RL-RH-BM alloys. The compositions of the obtained RL-RH-BM alloys are shown in Table 2.

[0052] [Table 2]

[0053] [Diffusion process] The RTB sintered magnet materials with the reference numbers 1-A to 1-D in Table 1 were cut and machined to obtain cubes of 7.2 mm x 7.2 mm x 7.2 mm. Next, an adhesive containing sugar alcohols was applied to the entire surface of the RTB sintered magnet material by dipping. RL-RH-BM alloy powder was attached to the RTB sintered magnet material coated with the adhesive at 3 mass% of the mass of the RTB sintered magnet material. Next, the RL-RH-BM alloy and the RTB sintered magnet material were heated in a vacuum heat treatment furnace at 900°C for 10 hours to carry out a diffusion process, and then cooled to obtain an RTB sintered magnet. The obtained RTB sintered magnet was subjected to heat treatment in a vacuum heat treatment furnace at 470°C to 530°C for 3 hours, and then cooled.

[0054] [Sample evaluation] The RTB sintered magnet material and the obtained samples (RTB sintered magnets after heat treatment) were analyzed using a BH tracer. r and H cJ The B of RTB sintered magnets was measured. r and H cJ The measurement results and the B r Value (B after diffusion r ) to RTB sintered magnet material B r Value (B before diffusion r ) is subtracted and the value is △B r The results are shown in Table 3. The components of the samples were measured using inductively coupled plasma optical emission spectroscopy (ICP-OES), and the results are shown in Table 4. As shown in Table 3, the comparative examples of Samples 1-5 to 1-8, in which alloys not containing B were diffused using Samples 1-A to 1-D, which are RTB sintered magnet materials, all had high H cJ Although B has been obtained r In contrast, in the examples of Samples 1-9 to 1-12 and Samples 1-17 to 1-22 in which the RL-RH-BM alloy was diffused using Samples 1-A to 1-D, which are RTB sintered magnet materials, all exhibited high H cJNot only has B been obtained, r It can be seen that the decrease in is small. r and H cJ Excellent balance of (B r While suppressing the decline of cJ In addition, in the comparative examples of Samples Nos. 1-13 to 1-16, in which the B content of the RL-RH-BM alloy is not within the appropriate range, the B content is r Although the decrease in H is small, it is still high enough. cJ It can be seen that this is not obtained. Additionally, individual pieces measuring 1 x 1 x 1 mm were cut from the magnet surface and interior of the samples, and inductively coupled plasma optical emission spectroscopy (ICP-OES) was used to examine "[T] / [B]", the gradual decrease in B concentration, and the gradual decrease in RH concentration. The results are shown in Table 3. Compared to the comparative examples of samples No. 1-5 to 1-8, in which an alloy not containing B was diffused, samples No. 1-9 to 1-22, in which an RL-RH-BM alloy was diffused, have a "[T] / [B]" of 0.2 or more lower on the magnet surface (center of the magnet) compared to the interior of the magnet, and it can be seen that there is also a gradual decrease in the B concentration.

[0055] [Table 3]

[0056] [Table 4]

[0057] Experimental Example 2 [Preparing RTB sintered magnet material (magnetic material)] Each element was weighed and cast by strip casting so as to obtain the composition of the magnet material shown in Table 5, which is indicated by symbols 2-A to 2-L, to obtain a flake-shaped raw alloy having a thickness of 0.2 to 0.4 mm. The obtained flake-shaped raw alloy was subjected to hydrogen pulverization, and then to a dehydrogenation treatment in which the alloy was heated to 550°C in a vacuum and then cooled to obtain a coarsely pulverized powder. The obtained coarsely pulverized powder was then pulverized using an airflow pulverizer (jet mill device) to obtain a finely pulverized powder (alloy powder) having a particle size D50 of 3 μm. The particle size D50 is the volume center value (volume-based median diameter) obtained by a laser diffraction method using an airflow dispersion method.

[0058] The finely pulverized powder was molded in a magnetic field to obtain a green body. The molding device used was a so-called perpendicular magnetic field molding device (horizontal magnetic field molding device) in which the magnetic field application direction and the pressure direction are perpendicular to each other.

[0059] The obtained green body was sintered in a vacuum at 1000°C to 1050°C (a temperature at which sufficient densification by sintering occurs for each sample) for 10 hours, and then quenched to obtain a magnetic material. The density of the obtained magnetic material was 7.5 Mg / m 3 That was all. Table 5 shows the results for the components of the obtained magnet material. Each component in Table 5 was measured using inductively coupled plasma optical emission spectroscopy (ICP-OES). The oxygen content of the magnet material was measured using a gas fusion-infrared absorption method, and it was confirmed that all were around 0.2 mass%. Furthermore, C (carbon content) was measured using a gas analyzer using the combustion-infrared absorption method, and it was confirmed that it was around 0.1 mass%.

[0060] [Table 5]

[0061] [Preparation of RL-RH-BM alloy] Each element was weighed so as to obtain the composition of the RL-RH-BM alloy and the composition of the alloy not containing B shown in Table 6, as indicated by symbols 2-a to 2-b, and the raw materials were melted and ribbon or flake-shaped alloys were obtained by a single-roll ultra-quenching method (melt spinning method). The obtained alloy was pulverized in an argon atmosphere using a mortar to prepare the RL-RH-BM alloy. The composition of the obtained RL-RH-BM alloy is shown in Table 6.

[0062] [Table 6]

[0063] [Diffusion process] The RTB sintered magnet materials with the reference numbers 2-A to 2-L in Table 5 were cut and machined to obtain cubes of 7.2 mm x 7.2 mm x 7.2 mm. Next, an adhesive containing sugar alcohols was applied to the entire surface of the RTB sintered magnet material by dipping. RL-RH-BM alloy powder was attached to the RTB sintered magnet material coated with the adhesive in an amount of 2 to 4 mass% based on the mass of the RTB sintered magnet material. Next, the RL-RH-BM alloy and the RTB sintered magnet material were heated in a vacuum heat treatment furnace at 900°C for 10 hours to carry out a diffusion process, and then cooled. After that, a heat treatment was carried out in a vacuum heat treatment furnace at 470°C to 530°C for 3 hours, and then cooled.

[0064] [Sample evaluation] The RTB sintered magnet material and the obtained samples (RTB sintered magnets after heat treatment) were analyzed using a BH tracer. r and H cJ The B of RTB sintered magnets was measured. r and H cJ The measurement results and the B r Value (B after diffusion r ) to RTB-based sintered magnet material B r Value (B before diffusion r ) is subtracted and the value is △B rThe results are shown in Table 7. The components of the samples were measured using inductively coupled plasma optical emission spectroscopy (ICP-OES), and the results are shown in Table 8. As shown in Table 7, the comparative examples of Samples No. 2-5 to 2-8, Samples No. 2-13 to 2-16, Samples No. 2-25 to 2-28, Samples No. 2-33 to 2-36, Samples No. 2-45 to 2-48, and Samples No. 2-53 to 2-56, in which alloys not containing B were diffused, all had high H cJ Although B has been obtained r In contrast, in the examples of Samples Nos. 2-9 to 2-12, 2-17 to 2-20, 2-29 to 2-32, 2-37 to 2-40, 2-49 to 2-52, and 2-57 to 2-60 in which the RL-RH-BM alloy was diffused using the RTB sintered magnet materials Samples Nos. 2-1 to 2-4, 2-21 to 2-24, and 2-41 to 2-44, all exhibited high H cJ Not only has B been obtained, r It can be seen that the decrease in is small. r and H cJ Thus, an RTB sintered magnet with an excellent balance of these properties has been obtained.

[0065] [Table 7]

[0066] [Table 8]

[0067] Experimental Example 3 [Preparing RTB sintered magnet material (magnetic material)] Each element was weighed and cast by strip casting so as to obtain the composition of the magnet material shown in Table 9, which is indicated by symbols 3-A and 3-B, to obtain a flake-shaped raw alloy having a thickness of 0.2 to 0.4 mm. The obtained flake-shaped raw alloy was subjected to hydrogen pulverization, and then to a dehydrogenation treatment in which the alloy was heated to 550°C in a vacuum and then cooled to obtain a coarsely pulverized powder. The obtained coarsely pulverized powder was then pulverized using an airflow pulverizer (jet mill device) to obtain a finely pulverized powder (alloy powder) having a particle size D50 of 3 μm. The particle size D50 is the volume center value (volume-based median diameter) obtained by a laser diffraction method using an airflow dispersion method.

[0068] The finely pulverized powder was molded in a magnetic field to obtain a green body. The molding device used was a so-called perpendicular magnetic field molding device (horizontal magnetic field molding device) in which the magnetic field application direction and the pressure direction are perpendicular to each other.

[0069] The obtained green body was sintered in a vacuum at 1000°C to 1050°C (a temperature at which sufficient densification by sintering occurs for each sample) for 10 hours, and then quenched to obtain a magnetic material. The density of the obtained magnetic material was 7.5 Mg / m 3 That was all. Table 9 shows the results of the components of the obtained magnet material. Each component in Table 9 was measured using inductively coupled plasma optical emission spectroscopy (ICP-OES). The oxygen content of the magnet material was measured using a gas fusion-infrared absorption method, and it was confirmed that all were around 0.2 mass%. Furthermore, C (carbon content) was measured using a gas analyzer using the combustion-infrared absorption method, and it was confirmed that it was around 0.1 mass%.

[0070] [Table 9]

[0071] [Preparation of RL-RH-BM alloy] Each element was weighed so as to obtain the composition of the RL-RH-BM alloys and the composition of the alloys not containing B shown in Table 10, which are indicated by symbols 3-a to 3-k, and the raw materials were melted and ribbon or flake-shaped alloys were obtained by a single-roll ultra-quenching method (melt spinning method). The obtained alloys were pulverized in an argon atmosphere using a mortar to prepare RL-RH-BM alloys. The compositions of the obtained RL-RH-BM alloys are shown in Table 10.

[0072] [Table 10]

[0073] [Diffusion process] The RTB sintered magnet materials with the reference numbers 3-A to 3-B in Table 9 were cut and machined to obtain cubes of 7.2 mm x 7.2 mm x 7.2 mm. Next, an adhesive containing sugar alcohols was applied to the entire surface of the RTB sintered magnet material by dipping. RL-RH-BM alloy powder was attached to the RTB sintered magnet material coated with the adhesive at 3 mass% of the mass of the RTB sintered magnet material. Next, the RL-RH-BM alloy and the RTB sintered magnet material were heated in a vacuum heat treatment furnace at 900°C for 10 hours to carry out a diffusion process, and then cooled. After that, a heat treatment was carried out in a vacuum heat treatment furnace at 470°C to 530°C for 1 hour, and then cooled.

[0074] [Sample evaluation] The RTB sintered magnet material and the obtained sample (RTB sintered magnet after heat treatment) were measured using a BH tracer. r and H cJ The B of RTB sintered magnets was measured. r and H cJ The measurement results and the B r Value (B after diffusion r ) to RTB sintered magnet material B r Value (B before diffusion r ) is subtracted and the value is △B r The results are shown in Table 11. In addition, the components of the samples were measured using inductively coupled plasma optical emission spectroscopy (ICP-OES), and the results are shown in Table 12. As shown in Table 11, the comparative examples of Sample No. 3-2, Sample No. 3-8, Sample No. 3-15, and Sample No. 3-21, which are RTB sintered magnet materials and in which alloys not containing B are diffused, all have high H cJ Although B has been obtained r In contrast, in the examples of Samples 3-3 to 3-7, 3-9 to 3-13, 3-16 to 3-20, and 3-22 to 3-26 in which the RL-RH-BM alloy was diffused using Samples 3-1 and 3-14, which are RTB sintered magnet materials, all exhibited high H cJ Not only has B been obtained, r It can be seen that the decrease in is small. r and H cJ The RTB sintered magnets obtained have an excellent balance of the above. In addition, 1x1x1mm pieces were cut from the magnet surface and the inside of the sample, and the "[T] / [B]" and the gradual decrease in B concentration and the gradual decrease in HR concentration were examined using inductively coupled plasma optical emission spectroscopy (ICP-OES). The results are shown in Table 11. In comparison with the comparative examples of samples No. 3-2, No. 3-8, No. 3-15, and No. 3-21 in which alloys not containing B were diffused, the "[T] / [B]" of the magnet surface is lower than that of the inside of the magnet for samples No. 3-3 to 3-7, No. 3-9 to 3-13, No. 3-16 to 3-20, and No. 3-22 to 3-26 in which RL-RH-BM alloys were diffused is also found to have a gradual decrease in B concentration.

[0075] [Table 11]

[0076] [Table 12]

[0077] Experimental Example 4 [Preparing RTB sintered magnet material (magnetic material)] Each element was weighed and cast by strip casting so as to obtain the composition of the magnet material shown in Table 13, which is indicated by reference numeral 4-A, to obtain a flake-shaped raw alloy having a thickness of 0.2 to 0.4 mm. The obtained flake-shaped raw alloy was subjected to hydrogen pulverization, and then to a dehydrogenation treatment in which the alloy was heated to 550°C in a vacuum and then cooled to obtain a coarsely pulverized powder. The obtained coarsely pulverized powder was then pulverized using an airflow pulverizer (jet mill device) to obtain a finely pulverized powder (alloy powder) having a particle size D50 of 3 μm. The particle size D50 is the volume center value (volume-based median diameter) obtained by a laser diffraction method using an airflow dispersion method.

[0078] The finely pulverized powder was molded in a magnetic field to obtain a green body. The molding device used was a so-called perpendicular magnetic field molding device (horizontal magnetic field molding device) in which the magnetic field application direction and the pressure direction are perpendicular to each other.

[0079] The obtained green body was sintered in a vacuum at 1000°C to 1050°C (a temperature at which sufficient densification by sintering occurs for each sample) for 10 hours, and then quenched to obtain a magnetic material. The density of the obtained magnetic material was 7.5 Mg / m 3 That was all. Table 13 shows the results of the components of the obtained magnet material. Each component in Table 13 was measured using inductively coupled plasma optical emission spectroscopy (ICP-OES). The oxygen content of the magnet material was measured using a gas fusion-infrared absorption method, and it was confirmed that all were around 0.2 mass%. Furthermore, C (carbon content) was measured using a gas analyzer using the combustion-infrared absorption method, and it was confirmed that it was around 0.1 mass%.

[0080] [Table 13]

[0081] [Preparation of RL-RH-BM alloy] Each element was weighed so as to obtain the composition of the RL-RH-BM alloys and the composition of the alloys not containing B shown in Table 14, which are indicated by symbols 4-a to 4-h, and the raw materials were melted and ribbon or flake-shaped alloys were obtained by a single-roll ultra-quenching method (melt spinning method). The obtained alloys were pulverized in an argon atmosphere using a mortar to prepare RL-RH-BM alloys. The compositions of the obtained RL-RH-BM alloys are shown in Table 14.

[0082] [Table 14]

[0083] [Diffusion process] The RTB sintered magnet material with reference number 4-A in Table 13 was cut and machined to a cube of 7.2 mm x 7.2 mm x 7.2 mm. Next, an adhesive containing sugar alcohols was applied to the entire surface of the RTB sintered magnet material by dipping. RL-RH-BM alloy powder was attached to the RTB sintered magnet material coated with the adhesive at 3 mass% of the mass of the RTB sintered magnet material. Next, the RL-RH-BM alloy and the RTB sintered magnet material were heated in a vacuum heat treatment furnace at 900°C for 10 hours to carry out a diffusion process, and then cooled. After that, heat treatment was carried out in a vacuum heat treatment furnace at 470°C to 530°C for 1 hour, and then cooled.

[0084] [Sample evaluation] The RTB sintered magnet material and the obtained samples (RTB sintered magnets after heat treatment) were analyzed using a BH tracer. r and H cJ The B of RTB sintered magnets was measured. r and H cJ The measurement results and the B r Value (B after diffusion r ) to RTB sintered magnet material B r Value (B before diffusion r ) is subtracted and the value is △B r The results are shown in Table 15. The components of the samples were measured using inductively coupled plasma optical emission spectroscopy (ICP-OES), and the results are shown in Table 16. As shown in Table 15, the comparative example of sample No. 4-2, in which an alloy not containing B was diffused into sample No. 4-1, which is an RTB sintered magnet material, showed high H cJ Although B has been obtained r In contrast, in the case of Sample No. 4-1, which is an RTB sintered magnet material, and Sample No. 4-3 to 4-9, which are examples in which an RL-RH-BM alloy is diffused, all show a high H cJ Not only has B been obtained, r It can be seen that the decrease in is small. r and H cJ The result is an RTB sintered magnet with an excellent balance of properties. Additionally, 1 x 1 x 1 mm individual pieces were cut from the magnet surface and interior of the sample magnet, and the "[T] / [B]" and the gradual decrease in B concentration, and the gradual decrease in HR concentration were examined using inductively coupled plasma optical emission spectroscopy (ICP-OES). The results are shown in Table 15. For samples No. 4-3 to 4-4 and No. 4-6 to 4-9, in which the RL-RH-BM alloy was diffused, the "[T] / [B]" is lower on the magnet surface compared to the interior of the magnet, and it can be seen that there is also a gradual decrease in the B concentration.

[0085] [Table 15]

[0086] [Table 16]

[0087] Experimental Example 5 [Preparing RTB sintered magnet material (magnetic material)] Each element was weighed and cast by strip casting so as to obtain the compositions of the magnet materials shown in Table 17, which are indicated by symbols 5-A to 5-D, to obtain flake-shaped raw alloys having a thickness of 0.2 to 0.4 mm. The obtained flake-shaped raw alloys were subjected to hydrogen pulverization, and then to a dehydrogenation treatment in which they were heated to 550°C in a vacuum and then cooled to obtain coarsely pulverized powder. The obtained coarsely pulverized powder was then pulverized using an airflow pulverizer (jet mill device) to obtain finely pulverized powder (alloy powder) having a particle size D50 of 3 μm. The particle size D50 is the volume center value (volume-based median diameter) obtained by a laser diffraction method using an airflow dispersion method.

[0088] The finely pulverized powder was molded in a magnetic field to obtain a green body. The molding device used was a so-called perpendicular magnetic field molding device (horizontal magnetic field molding device) in which the magnetic field application direction and the pressure direction are perpendicular to each other.

[0089] The obtained green body was sintered in a vacuum at 1000°C to 1050°C (a temperature at which sufficient densification by sintering occurs was selected for each sample) for 10 hours, and then rapidly cooled to obtain a magnetic material. The density of the obtained magnetic material was 7.5 Mg / m 3 That was all. Table 17 shows the results of the components of the obtained magnet material. Each component in Table 17 was measured using inductively coupled plasma optical emission spectroscopy (ICP-OES). The oxygen content of the magnet material was measured using a gas fusion-infrared absorption method, and it was confirmed that all were around 0.2 mass%. Furthermore, C (carbon content) was measured using a gas analyzer using the combustion-infrared absorption method, and it was confirmed that it was around 0.1 mass%.

[0090] [Table 17]

[0091] [Preparation of RL-RH-BM alloy] Each element was weighed so as to obtain the composition of the RL-RH-BM alloy shown in Table 18, which is indicated by symbols 5-a to 5-e, and the raw materials were melted and a ribbon or flake-shaped alloy was obtained by a single-roll ultra-quenching method (melt spinning method). The obtained alloy was pulverized in an argon atmosphere using a mortar to prepare the RL-RH-BM alloy. The composition of the obtained RL-RH-BM alloy is shown in Table 18.

[0092] [Table 18]

[0093] [Diffusion process] The RTB sintered magnet materials with the reference numbers 5-A to 5-D in Table 17 were cut and machined to obtain cubes of 7.2 mm x 7.2 mm x 7.2 mm. Next, an adhesive containing sugar alcohols was applied to the entire surface of the RTB sintered magnet material by dipping. RL-RH-BM alloy powder was attached to the RTB sintered magnet material coated with the adhesive at 3 mass% of the mass of the RTB sintered magnet material. Next, the RL-RH-BM alloy and the RTB sintered magnet material were heated in a vacuum heat treatment furnace at 900°C for 10 hours to carry out a diffusion process, and then cooled. After that, a heat treatment was carried out in a vacuum heat treatment furnace at 470°C to 530°C for 1 hour, and then cooled.

[0094] [Sample evaluation] The RTB sintered magnet material and the obtained samples (RTB sintered magnets after heat treatment) were analyzed using a BH tracer. r and H cJ The B of RTB sintered magnets was measured. r and H cJ The measurement results and the B r Value (B after diffusion r ) to RTB sintered magnet material B r Value (B before diffusion r ) is subtracted and the value is △B r The results are shown in Table 19. In addition, the components of the samples were measured using inductively coupled plasma optical emission spectroscopy (ICP-OES), and the results are shown in Table 20. As shown in Table 19, the RTB sintered magnet materials Sample No. 5-1, Sample No. 5-7, Sample No. 5-11, and Sample No. 5-14 were used to diffuse the RL-RH-BM alloy, and the examples of Sample Nos. 5-2 to 5-6, 5-8 to 5-10, 5-12 to 5-13, and 5-15 to 5-16 all showed high H cJ Not only has B been obtained, r It can be seen that the decrease in is small. r and H cJ The result is an RTB sintered magnet with an excellent balance of properties. In addition, 1 x 1 x 1 mm individual pieces were cut from the magnet surface and interior of the samples, and the "[T] / [B]" and the gradual decrease in B concentration and gradual decrease in HR concentration were examined using inductively coupled plasma optical emission spectroscopy (ICP-OES). The results are shown in Table 19. For samples No. 5-2 to 5-6, No. 5-8 to 5-10, No. 5-12 to 5-13, and No. 5-15 to 5-16, in which RL-RH-BM alloys were diffused, the "[T] / [B]" ratio on the magnet surface was 0.2 or more lower than the interior of the magnet, and it can be seen that there was also a gradual decrease in the B concentration.

[0095] [Table 19]

[0096] [Table 20]

[0097] Experimental Example 6 [Preparing RTB sintered magnet material (magnetic material)] Each element was weighed and cast by strip casting so as to obtain the composition of the magnet material shown in Table 21, reference numeral 6-A, to obtain a flake-shaped raw alloy having a thickness of 0.2 to 0.4 mm. The obtained flake-shaped raw alloy was subjected to hydrogen pulverization, and then to a dehydrogenation treatment in which the alloy was heated to 550°C in a vacuum and then cooled to obtain a coarsely pulverized powder. The obtained coarsely pulverized powder was then pulverized using an airflow pulverizer (jet mill device) to obtain a finely pulverized powder (alloy powder) having a particle size D50 of 3 μm. The particle size D50 is the volume center value (volume-based median diameter) obtained by a laser diffraction method using an airflow dispersion method.

[0098] The finely pulverized powder was molded in a magnetic field to obtain a green body. The molding device used was a so-called perpendicular magnetic field molding device (horizontal magnetic field molding device) in which the magnetic field application direction and the pressure direction are perpendicular to each other.

[0099] The obtained green body was sintered in a vacuum at 1000°C to 1050°C (a temperature at which sufficient densification by sintering occurs was selected for each sample) for 10 hours, and then rapidly cooled to obtain a magnetic material. The density of the obtained magnetic material was 7.5 Mg / m 3 That was all. Table 21 shows the results of the components of the obtained magnet material. Each component in Table 21 was measured using inductively coupled plasma optical emission spectroscopy (ICP-OES). The oxygen content of the magnet material was measured using a gas fusion-infrared absorption method, and it was confirmed that all were around 0.2 mass%. Furthermore, C (carbon content) was measured using a gas analyzer using the combustion-infrared absorption method, and it was confirmed that it was around 0.1 mass%.

[0100] [Table 21]

[0101] [Preparation of RL-RH-BM alloy] Each element was weighed so as to obtain the composition of the RL-RH-BM alloys and the composition of the alloys not containing B shown in Table 22, which are indicated by symbols 6-a to 6-j, and the raw materials were melted and ribbon or flake-shaped alloys were obtained by a single-roll ultra-quenching method (melt spinning method). The obtained alloys were pulverized in an argon atmosphere using a mortar to prepare RL-RH-BM alloys. The compositions of the obtained RL-RH-BM alloys are shown in Table 22.

[0102] [Table 22]

[0103] [Diffusion process] The RTB sintered magnet material with reference number 6-A in Table 21 was cut and machined to a cube of 7.2 mm x 7.2 mm x 7.2 mm. Next, an adhesive containing sugar alcohols was applied to the entire surface of the RTB sintered magnet material by dipping. RL-RH-BM alloy powder was attached to the RTB sintered magnet material coated with the adhesive at 3 mass% of the mass of the RTB sintered magnet material. Next, the RL-RH-BM alloy and the RTB sintered magnet material were heated in a vacuum heat treatment furnace at 900°C for 10 hours to carry out a diffusion process, and then cooled. After that, heat treatment was carried out in a vacuum heat treatment furnace at 470°C to 530°C for 1 hour, and then cooled.

[0104] [Sample evaluation] The RTB sintered magnet material and the obtained samples (RTB sintered magnets after heat treatment) were analyzed using a BH tracer. r and H cJ The B of RTB sintered magnets was measured. r and H cJ The measurement results and the B r Value (B after diffusion r ) to RTB sintered magnet material B r Value (B before diffusion r ) is subtracted and the value is △B rThe results are shown in Table 23. The components of the samples were measured using inductively coupled plasma optical emission spectroscopy (ICP-OES), and the results are shown in Table 24. As shown in Table 23, the comparative examples of Sample No. 6-3, Sample No. 6-5, Sample No. 6-7, and Sample No. 6-11, in which alloys not containing B were diffused into Sample No. 6-1, an RTB sintered magnet material, all exhibited high H cJ Although B has been obtained r In contrast, in the examples of Sample No. 6-2, Sample No. 6-4, Sample No. 6-6, and Sample Nos. 6-8 to 6-10, in which the RL-RH-BM alloy was diffused into Sample No. 6-1, which is an RTB sintered magnet material, all exhibited high H cJ Not only has B been obtained, r It can be seen that the decrease in is small. r and H cJ The RTB sintered magnets obtained have an excellent balance of the above. In addition, 1x1x1mm pieces were cut from the magnet surface and the inside of the sample, and the "[T] / [B]" and the gradual decrease in B concentration and the gradual decrease in HR concentration were examined using inductively coupled plasma optical emission spectroscopy (ICP-OES). The results are shown in Table 23. Compared to the comparative examples of Sample No. 6-3, Sample No. 6-5, Sample No. 6-7, and Sample No. 6-11 in which alloys not containing B were diffused, Sample No. 6-2, Sample No. 6-4, Sample No. 6-6, and Sample Nos. 6-8 to 6-10 in which RL-RH-BM alloys were diffused have a lower "[T] / [B]" on the magnet surface compared to the inside of the magnet, and there is also a gradual decrease in the B concentration.

[0105] [Table 23]

[0106] [Table 24]

[0107] 12 R2T14 Main phase consisting of B compounds 14 Grain boundary phase 14a Two-grain grain boundary phase 14b Grain boundary triple point

Claims

1. preparing an R-T-B based sintered magnet material (R is a rare earth element and must contain at least one selected from the group consisting of Nd, Pr, and Ce, and T is at least one selected from the group consisting of Fe, Co, Al, Mn, and Si, and must contain Fe); A step of preparing an RL-RH-B-M based alloy (RL is a light rare earth element and necessarily contains at least one selected from the group consisting of Nd, Pr and Ce, RH is at least one selected from the group consisting of Tb, Dy and Ho, B is boron, and M is at least one selected from the group consisting of Cu, Ga, Fe, Co, Ni, Al, Ag, Zn, Si and Sn); a diffusion step of adhering at least a part of the RL-RH-B-M based alloy to at least a part of the surface of the sintered R-T-B based magnet material, and heating the resulting material at a temperature of 700° C. or higher and 1100° C. or lower in a vacuum or inert gas atmosphere; The RL-RH-B-M based alloy has an RL content of 50 mass% or more and 95 mass% or less, an RH content of 45 mass% or less (including 0 mass%), a B content of 0.1 mass% or more and 3.0 mass% or less, and an M content of 4 mass% or more and 49.9 mass% or less.

2. 2. The method for producing a sintered R-T-B based magnet according to claim 1, wherein the molar ratio of T to B, [T] / [B], in the sintered R-T-B based magnet material is greater than 14.0 and not greater than 15.

0.

3. 3. The method for producing an R-T-B based sintered magnet according to claim 1, wherein M in the RL-RH-B-M based alloy contains at least one of Cu, Ga, and Fe, and the total content of Cu, Ga, and Fe in M ​​is 80 mass% or more.

4. An R-T-B based sintered magnet containing R (R is a rare earth element and necessarily includes at least one selected from the group consisting of Nd, Pr, and Ce), T (T is at least one selected from the group consisting of Fe, Co, Al, Mn, and Si and necessarily includes Fe), B, and at least one selected from the group consisting of Cu, Ga, Ni, Ag, Zn, and Sn, wherein the molar ratio of T to B in a surface portion of the magnet [T] / [B] is lower than the molar ratio of T to B in a central portion of the magnet [T] / [B].

5. 5. The R-T-B based sintered magnet according to claim 4, which includes a portion in which the B concentration gradually decreases from the magnet surface toward the magnet interior.

6. 6. The R-T-B based sintered magnet according to claim 4, wherein the molar ratio of T to B [T] / [B] at a surface portion of the magnet is at least 0.2 lower than the molar ratio of T to B [T] / [B] at a central portion of the magnet.

7. 7. The R-T-B based sintered magnet according to claim 4, wherein the Tb content in the R-T-B based sintered magnet is less than 0.5 mass % (including 0 mass %).

Citation Information

Patent Citations

  • Process for producing rare earth permanent magnet material

    JP2007287875A

  • Method for manufacturing r-t-b-based sintered magnet

    JP2012234971A

  • Method for manufacturing r-t-b based sintered magnet

    JP2020120102A

  • R-t-b sintered magnet and production method therefor

    US20190326053A1

  • Method for producing sintered r-t-b based magnet

    US20200243234A1